2023
DOI: 10.3389/fimmu.2022.1028890
|View full text |Cite
|
Sign up to set email alerts
|

Subjective sleep quality and fatigue assessment in Polish adult patients with primary immunodeficiencies: A pilot study

Abstract: IntroductionPrimary immunodeficiencies (PIDs) are clinically heterogeneous disorders caused by abnormalities in the immune system. However, PIDs are genetically determined and may occur at any age from early childhood to elderly age. Due to chronic patterns, the risk of malignancy and organ damage in patients with PIDs may affect any aspect of life, including sleep patterns. To our knowledge, the prevalence of insomnia and subjective sleep quality have not been investigated in patients with PIDs. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
4
1
Order By: Relevance
“…(2) > (0), patients declaring pain occurring more than 30 days in the previous 3 months had significantly higher level of anxiety than patients declaring no pain. Previously, we revealed that 38% of patients with IEI had anxiety symptoms, which were more frequent than depression symptoms (3). In this study, no correlations were detected between the activity of the disease and the anxiety levels.…”
Section: Anxietycontrasting
confidence: 66%
See 4 more Smart Citations
“…(2) > (0), patients declaring pain occurring more than 30 days in the previous 3 months had significantly higher level of anxiety than patients declaring no pain. Previously, we revealed that 38% of patients with IEI had anxiety symptoms, which were more frequent than depression symptoms (3). In this study, no correlations were detected between the activity of the disease and the anxiety levels.…”
Section: Anxietycontrasting
confidence: 66%
“…However, some studies revealed that anxiety is potentially more prevalent than depression among patients with IEI (20), and it is often overlooked in clinical practice. In our previous study (3), which included a part of the current study (n=92), anxiety symptoms were frequent. Therefore, we expanded our sample (n=105) and considered anxiety as a dependent variable to perform a more precise analysis of factors, including anxiety levels, the association of anxiety levels with sleeping disorders, and pain.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations